Una lectura de caballo y tren (1954) de Alex Colville aumento de lo visible - Trottier, Hélene (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
Throughout the Canadian painter's work Alex Colville (born in Toronto, Ontario, in1920) that although it is not very numerous, yes it is constant, we find a presence important of animals, as much in number as in relevance. 2 with their realism existential Colville gives tribute to the reality and it shares it with the spectator. This realism is about the relationships that one has with its dear beings, with its mean, with their exist, with the nature, with the animals 3. The windows that the painter opens up in the one forgetfulness of the daily thing, of the ordinary thing, they take to the spectator to direct a look more attentive and fresh about what lies inadvertent, and inside this category they are included to the animals. Their work allows us to do the daily thing with the power of increase of a microscope, taking the small thing, the tiny thing, that forgotten, to other proportions, giving it a real and fair importance. What is the ordinary thing? It is it... ordinary. It is so ordinary that he/she won't have bigger definition? It is so... ordinary that no longer needs of presentations. We all know to know it, to recognize it, to experience it, and to forget it. It is it that to the question. What did you make today? One responds .Nada it is it that every day ago, what repeats, him that he/she becomes routine, until boredom, but that if he/she would have opportunity it could become important, outstanding, reflexive. It is debo in answer to all other option.

A lo largo de la obra del pintor canadiense Alex Colville (nacido en Toronto, Ontario, en 1920) que si bien no es muy numerosa, sí es constante, encontramos una presencia importante de animales, tanto en número como en relevancia. 2 Con su realismo existencial Colville da tributo a la realidad y lo comparte con el espectador. Este realismo trata de las relaciones que uno tiene con sus seres queridos, con su medio, con su existir, con la naturaleza, con los animales 3. Las ventanas que el pintor abre en el olvido de lo cotidiano, de lo ordinario, llevan al espectador a dirigir una mirada más atenta y fresca acerca de lo que yace inadvertido, y dentro de esta categoría se incluyen a los animales. Su obra nos permite ver lo cotidiano con el poder de aumento de un microscopio, llevando lo pequeño, lo diminuto, lo olvidado, a otras proporciones, dándolo una real y justa importancia. ¿Qué es lo ordinario? Es lo... ordinario. ¿Es tan ordinario que no tendrá mayor definición? Es tan... ordinario que ya no necesita de presentaciones. Todos sabemos conocerlo, reconocerlo, experimentarlo, y olvidarlo. Es lo que a la pregunta ― ¿Qué hiciste hoy?‖ se responde ―Nada‖. Es lo que se hace todos los días, lo que se repite, lo que se vuelve rutina, hasta aburrimiento, pero que sí tendría oportunidad podría volverse importante, relevante, reflexivo. Es el ―debo‖ en respuesta a toda otra opción.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2011-0037; Artista; Realismo; Alex Colville; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/67